Genome-wide analysis of the MADS-box gene family in Brachypodium distachyon. - Bo Wei (Public Library of Science (PLoS), 2014)
MADS-box genes are important transcription factors for plant development, especially floral organogenesis. Brachypodium distachyon is a model for biofuel plants and temperate grasses such as wheat and barley, but a comprehensive analysis of MADS-box family proteins in Brachypodium is still missing. We report here a genome-wide analysis of the MADS-box gene family in Brachypodium distachyon. We identified 57 MADS-box genes and classified them into 32 MIKC(c)-type, 7 MIKC*-type, 9 Mα, 7 Mβ and 2 Mγ MADS-box genes according to their phylogenetic relationships to the Arabidopsis and rice MADS-box genes. Detailed gene structure and motif distribution were then studied. Investigation of their chromosomal localizations revealed that Brachypodium MADS-box genes distributed evenly across five chromosomes. In addition, five pairs of type II MADS-box genes were found on synteny blocks derived from whole genome duplication blocks. We then performed a systematic expression analysis of Brachypodium MADS-box genes in various tissues, particular floral organs. Further detection under salt, drought, and low-temperature conditions showed that some MADS-box genes may also be involved in abiotic stress responses, including type I genes. Comparative studies of MADS-box genes among Brachypodium, rice and Arabidopsis showed that Brachypodium had fewer gene duplication events. Taken together, this work provides useful data for further functional studies of MADS-box genes in Brachypodium distachyon.